Practical tips for treatment of radiation-induced toxicity in patients during and after radiotherapy due to locally advanced breast cancer - Chałubińska, Justyna; Spych, Michał; Łuniewska-Bury, Jolanta; Fijuth, Jacek (Menopause Review/Przegląd Menopauzalny, 2011)
Breast cancer is the most common type of malignancy among women in the Polish population. A majority of breast cancer patients require radiotherapy and some of them suffer from radiation-related toxicity. The symptoms of radiotherapy toxicity manifest as acute injuries during the initial 3 months after treatment and late toxicities that occur after 6 months following radiotherapy. Local toxicity due to breast cancer irradiation mostly develops in the form of light skin injury, fibrosis and adiponecrosis, and sporadically as telangiectasia or bleeding ulcer. Adiponecrosis may imitate malignancy and may necessitate further diagnostic procedures. The article presents factors which play significant roles in inducing radiation toxicity due to breast cancer radiotherapy. The paper also outlines practical tips how non-oncologists can prevent and cope with radiation-induced toxicities occurring on skin and breast fat tissue in patients undergoing radiotherapy of that region. Diagnostic tools most useful in differentiating adiponecrosis from a malignant process are also enumerated and discussed in depth. The issue of the importance of a multispecialist team – one including surgeons, oncologists and physiotherapists – in coping with radiotherapy-induced toxicities is also discussed.